(untitled) (Fiep Bulletin - online, 2016)
This article relates to research conducted at school from the state education system of Joinville (SC) and aimed to analyze if the work performed by the Physical Education teacher favors the inclusion of students with disabilities in their classes. For realization of this study, a descriptive field research, case study type, a qualitative analysis was performed. The present study included three physical education teachers, who work in the institution researched. In obtaining the data, as research tools, the adapted questionnaire were used for Marques (2000), direct observation of classes with registers in a field diary and reading of the lesson plans. As a technique for information analysis the obtained was used content analysis (FRANCO, 2008). The data allow us to say that the inclusion of students with disabilities in regular physical education classes occurs partially, in other words, at certain times of the class, as developed activity. The fact that the initial teacher formation don’t have access to content that qualification working with students with disabilities, as well as the fragility of continuing education, which lacks such content, collaborate on the evidence of this structure. For teachers, in addition to the update, there is a need for educational support and adequate resources. We understand that these will work for the teacher values ??the potential of the student and not a limitation for inclusion to happen.